Endophytic Bacillus subtilis antagonize soil-borne fungal pathogens and suppress wilt complex disease in chickpea plants (Cicer arietinum L.) - Mageshwaran, Vellaichamy; Gupta, Rishabh; Singh, Shailendra; Sahu, Pramod K.; Singh, Udai B.; Chakdar, Hillol; Bagul, Samadhan Y.; Paul, Surinder; Singh, Harsh V. (Frontiers in Microbiology, 2022)
The present study aimed to identify potential endophytic bacteria antagonistic against three soil-borne fungal pathogens, Rhizoctonia solani, Sclerotium rolfsii, and Fusarium oxysporum f.sp. ciceri causing root rot, collar rot, and fungal wilt diseases in chickpea plants, respectively. A total of 255 bacterial endophytes were isolated from the leaves, stems, and roots of seven different crop plants (chickpea, tomato, wheat, berseem, mustard, potato, and green pea). The dual culture-based screening for antifungal properties indicated that three endophytic isolates had strong inhibition (>50%) against all three pathogens tested. Based on morphological, biochemical, and molecular characterization, the selected isolates (TRO4, CLO5, and PLO3) were identified as different strains of Bacillus subtilis. The bacterial endophytes (TRO4 and CLO5) were positive for plant growth promoting (PGP) traits viz., ammonia, siderophore, and indole-3-acetic acid (IAA) production. The bio-efficacy of the endophytes (TRO4, CLO5, and PLO3) was tested by an in planta trial in chickpea pre-challenged with R. solani, S. rolfsii, and F. oxysporum f.sp. ciceri. The B. subtilis strains TRO4 and CLO5 were found to be effective in reducing percent disease incidence (p ≤ 0.05) and enhancing plant growth parameters. The different root parameters viz. root length (mm), surface area (cm2), root diameter (mm), and root volume (cm3) were significantly (p ≤ 0.05) increased in TRO4 and CLO5 inoculated chickpea plants. Confocal Scanning Laser Microscopy showed heavy colonization of bacteria in the roots of endophyte-inoculated chickpea plants. The inoculation of endophytic Bacillus subtilis strains TRO4 and CLO5 in chickpea plants through seed biopriming reduced the accumulation of superoxide, enhanced the plant defense enzymes, and induced the expression of Pathogenesis-Related (PR) genes. Semi-quantitative analysis of defense-related genes showed differential activation of PR genes (60srp and IFR) by endophyte inoculation. The results of the present study reveal the antagonistic potential of B. subtilis strains TRO4 and CLO5 against three major soil-borne fungal pathogens and their ability to suppress wilt complex disease in chickpea plants. This is the first report on the simultaneous suppression of three major soil-borne fungal pathogens causing wilt complex in chickpea plants by endophytic B. subtilis strains.